PREVALENCE OF PAANDU (ANAEMIA) AMONGST PATIENTS REPORTING AT OUTPATIENT DEPARTMENT OF NATIONAL INSTITUTE OF SIDDHA (International Journal of Ayurveda and Pharma Research, 2019)
Anaemia is the most common nutritional problem in the world .In the outpatient department of National institute of Siddha the significant numbers of anaemia cases are reporting for treatment. As the part of partial completion of 1st year MD degree the investigator select the minor project to determine the data about prevalence of Paandu (Anaemia) in NIS OPD patients. This study includes 500 OPD patients. OPD patients in the age between 13-74 years were randomly selected daily (Systematic random sampling method). A pre-designed self-administrated questionnaire interview method is used for collecting data about the patients. Information on personal characteristics, socio economic status, diet, lab investigations, clinical profiles are obtained. The study results showed that the prevalence of anemia amongst patients reporting at NIS OPD were 45.6%. The mean haemoglobin concentration was 11.4g/dl in female and 12.8g/dl in male. Majority of female in reproductive age (15-49 years) had the highest prevalence of anemia. And the high proportion of microcytic hypochromic anaemia (22.2%) was founded in the selected samples which indicate that Iron deficiency was the main cause of anaemia. Effect of socio economic status on anemic patients reported in NIS also calculated according to ‘Modified Kuppusamy socio economic scale’ which results that patients belongs to the upper lower status (12.2%) are more prone to anemia. Therefore the results of this study can be used to design target interventions aimed at reducing the prevalence of anemia in NIS OPD and to help conduct the interactive educational programs for improve disease awareness in female patients especially. And further studies are needed for clarify prevalence and etiology of anaemia in school going children (Below 13 years) at NIS OPD.